Peran Asas Dubio Pro Reo dalam Pasar Pertimbangan Putusan Bebas (Vrijspraak) pada Kasus Pemerkosaan dan Pembunuhan: (Studi Putusan Nomor : 155/Pid/2020/PT TJK) - Budi Rizki Husin; Fransisca Emilia; Maroni Maroni (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
The in dubio pro reo principle is a fundamental principle in criminal law that states that if there is doubt in the proof of a case, then the decision must be taken in favor of the defendant. The application of this principle is particularly crucial in rape and murder cases, where the legal consequences faced by the accused are severe. However, the use of this principle often causes debate because it can have an impact on the sense of justice for victims and society. This research uses a normative qualitative method with a normative juridical approach to analyze laws and regulations, legal doctrines, and court decisions related to the application of the in dubio pro reo principle. Data was collected through literature study by analyzing relevant court decisions. The results showed that the application of this principle is based on the negatief wettelijk evidentiary system, which requires a minimum of two valid pieces of evidence and the judge's conviction to impose a sentence. However, in practice, the difficulty of proof in rape and murder cases can lead to the defendant being acquitted despite indications of guilt. Therefore, the balance between the protection of the defendant's rights and justice for the victim must be considered in the application of this principle.